Discovering Our Gifts from Nature Now and in the Future. Part II - Cordell, Geoffrey A. (2003)
Traditional medicine, the use of plants, animals, and minerals for human health needs must be brought toa new scientific level of sustainable development in order to accommodate future global health care needs.